PENGARUH GOAL SETTING TERHADAP PERFORMANCE : TINJAUAN TEORITIS - Surya Dharma Ginting; D. Wahyu Ariani (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2004)
This article is the conceptual view of goal setting theory and effects of goal setting on individual performance. Goal setting is recognized, and is a major theory of work motivation. Difficult goals have consistently been shown to lead to higher levels of performance than easy goals. If there is no commitment, a goal can have no motivational effect. Goals are central to current treatments of work motivation, and goal commitment is a necessary condition for difficult goals to result in higher task performance.Keywords : goals, goal-setting theory, performance